2021
DOI: 10.1021/acs.joc.0c03044
|View full text |Cite
|
Sign up to set email alerts
|

Acetal Addition to Electron-Deficient Alkenes with Hydrogen Atom Transfer as a Radical Chain Propagation Step

Abstract: We describe a visible-light-promoted addition of a hydrogen atom and an acetal carbon toward various electrondeficient alkenes. 1,3-Dioxolane is converted to its radical species in the presence of persulfate and an iridium catalyst upon visible light irradiation, which then reacts with electron-deficient alkenes. The reaction operates via a radical chain mechanism, a less commonly observed pathway for this class of transformation. Hydrogen atom transfer from 1,3-dioxolane to α-malonyl radicals is corroborated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…35 Further investigations by Koide showed that dioxolane addition mediated by persulfate is activated in the presence of an iridium photocatalyst and visible light irradiation. 36 More recently, MacMillan 37 and Doyle 38 independently used iridium-based visible light photoredox catalysis to generate active radical species which were employed in Minisci-type reactions and in Ni-catalyzed coupling reactions with aryl chlorides, respectively. The more recent approaches have in common the use of metal-based photoredox catalysts.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…35 Further investigations by Koide showed that dioxolane addition mediated by persulfate is activated in the presence of an iridium photocatalyst and visible light irradiation. 36 More recently, MacMillan 37 and Doyle 38 independently used iridium-based visible light photoredox catalysis to generate active radical species which were employed in Minisci-type reactions and in Ni-catalyzed coupling reactions with aryl chlorides, respectively. The more recent approaches have in common the use of metal-based photoredox catalysts.…”
mentioning
confidence: 99%
“…In 2011, Fagnoni reported that Michael acceptors underwent addition by dioxolane in the presence of tetrabutylammonium decatungstate salt as a photocatalyst under UV irradiation . Further investigations by Koide showed that dioxolane addition mediated by persulfate is activated in the presence of an iridium photocatalyst and visible light irradiation . More recently, MacMillan and Doyle independently used iridium-based visible light photoredox catalysis to generate active radical species which were employed in Minisci-type reactions and in Ni-catalyzed coupling reactions with aryl chlorides, respectively.…”
mentioning
confidence: 99%
“…Therefore, they are recognized as masked aldehydes, which could be converted into the corresponding aldehydes after hydrolysis. 59…”
Section: Photocatalytic Hat Of 13-dioxolane To Synthesize Aldehydesmentioning
confidence: 99%
“…The Koide group reported the direct addition of acetal carbon 201a into various electron-deficient olefins 201b (Scheme 201). 310 In the presence of visible light, the persulfate and an iridium photocatalyst trigger the generation of 1,3-dioxolane radical species. Subsequently, addition into the olefins to form α-malonyl radicals 201c , followed by hydrogen atom transfer (HAT) from 1,3-dioxolane to α-malonyl radicals, further propagates the reaction.…”
Section: Transition-metal-based Photocatalytic Alkylationmentioning
confidence: 99%